2018
DOI: 10.1590/1678-4162-9861
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the stx1 and stx2 genes in Escherichia coli isolated from milk cattle according to season, age, and production scale in southwestern region of Goiás, Brazil

Abstract: This study determined the distribution of stx1 and stx2 genes in Escherichia coli isolated from dairy herds with regard to animal age, season, and farm production-scale, and analyzed the phylogenetic distribution of the groups A, B1, B2, and D of 276 isolates of bovine feces Shiga toxin-producing E. coli (STEC). The stx1 profile was the most common, detected in 20.4% (202/990) of the isolates, followed by stx2 (4.54%, 45/990) and stx1+stx2 (2.92%, 29/990). The stx1 gene was detected more frequently in calves t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
1
7
0
1
Order By: Relevance
“…This farm had a high occurrence of isolates containing the gene stx2 in milk and feces samples, and one isolate in water samples. In this property, there might have been cross-contamination among animal feces, milking parlor water, and raw milk due to high environmental contamination, demonstrating the need for hygienic practices (36) .…”
Section: Resultsmentioning
confidence: 99%
“…This farm had a high occurrence of isolates containing the gene stx2 in milk and feces samples, and one isolate in water samples. In this property, there might have been cross-contamination among animal feces, milking parlor water, and raw milk due to high environmental contamination, demonstrating the need for hygienic practices (36) .…”
Section: Resultsmentioning
confidence: 99%
“…Cattle are the major STEC reservoir, and beef has been essentially identified as the main vehicle associated with the transmission of this group of microorganisms [52]. The mean stx prevalence in cattle estimated by the QMRA (25.1%, 6.2-64.4%, 95.0% CI) was in the range of that reported in Brazil, USA, Italy and Spain (21.3-36.2%) [87][88][89][90][91]. The STEC prevalence reported in studies conducted in Argentina is also within the same range (11.8-38.9%) [38,39,52,53].…”
Section: Cattle Primary Productionmentioning
confidence: 87%
“…Pervez et al, [32] reported that 10% of the isolates of calves were positive for VT1 gene while eaeA not detected. The VT1 gene was detected more frequently in calves than in adult animals [40].…”
Section: Discussionmentioning
confidence: 95%